Review of electrical design of animal containment project at Rawdat Al Faras, Zubara, Qatar - Zumarraga, Ferdinand Joy O.
This report shows the calculation of loads, voltage drops of cables from Transformer to Distribution Boards. It also shows the size of Overcurrent Protective Devices (OCPD) and size of cables to be installed. For cables sizes and circuit breaker ratings, the calculations are based from NEC 2014 and PEC 2009. Short circuit calculation from transformer to main breaker of motors (Drainage Pumps) was also done. Protection coordination is performed to illustrate the circuit breaker time-current curves and to select the appropriate circuit breaker ratings and type from Main Distribution Board-ACB to the main breaker of drainage pumps. Fire pump calculation is also explained based on Article 695 of NEC and PEC. The final Single Line Diagram shows some changes in the size of cables and protective devices. The conclusion and recommendations are also written in the last part of this report.